2016
DOI: 10.1002/jaoc.12014
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Efficacy Among Adults in Substance Abuse Treatment: The Role of Religious Coping

Abstract: In substance abuse treatment, general self-efficacy and religiousness are factors that may support positive outcomes. The authors surveyed clients receiving substance abuse treatment (N = 121) and found that religious coping predicted general self-efficacy scores. Clinical implications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
2
10
0
1
Order By: Relevance
“…The vertical relationship formed between the individual and the God becomes very powerful in directing behavior. Giordano, Prosek, Daly, Holm, Ramsey Abernathy, & Sender (2015); Giordano, Prosek, Loseu, Bevly, Stamman, Molina, Callahan, & Calzada (2016) support the findings of this research, religion being the way to solve the problem of drug abuse. The role of the authorities is very important if people find drug abuse cases.…”
Section: Resultssupporting
confidence: 83%
“…The vertical relationship formed between the individual and the God becomes very powerful in directing behavior. Giordano, Prosek, Daly, Holm, Ramsey Abernathy, & Sender (2015); Giordano, Prosek, Loseu, Bevly, Stamman, Molina, Callahan, & Calzada (2016) support the findings of this research, religion being the way to solve the problem of drug abuse. The role of the authorities is very important if people find drug abuse cases.…”
Section: Resultssupporting
confidence: 83%
“…In the explanation of the school counselors, the existing modules still need improvement due to incomplete and less up to date material, not adapted to the reality in the field, lack of information about actions that can be taken if there are students who are known to have committed drug abuse and it is necessary to include a religious perspective in discussions about drugs. Religious perspective needed to include in the module because as explained by Giordano et al In substance abuse treatment, general self-efficacy and religiousness are factors that may support positive outcomes [13].…”
Section: Resultsmentioning
confidence: 99%
“…Not only did these researchers combine lesbian and bisexual female adolescents as one homogeneous group, they used a sexual behavior identifier (not sexually active) to categorize sexual orientation. Another study explored self-efficacy among adults in substance abuse treatment (Giordano, Prosek, Loseu, et al, 2016). Although Giordano, Prosek, Loseu, et al (2016) did not include sexual orientation as a construct to be analyzed, they reported that eight of the 121 participants in their sample were gay (6.6%), nine were bisexual (7.4%), and 103 were heterosexual (85.1%), with one participant not reporting (0.8%).…”
Section: Nbgi Reported Comments About Studymentioning
confidence: 99%
“…Another study explored self-efficacy among adults in substance abuse treatment (Giordano, Prosek, Loseu, et al, 2016). Although Giordano, Prosek, Loseu, et al (2016) did not include sexual orientation as a construct to be analyzed, they reported that eight of the 121 participants in their sample were gay (6.6%), nine were bisexual (7.4%), and 103 were heterosexual (85.1%), with one participant not reporting (0.8%). Notable is that the category "gay" could include gay men or lesbians, and "bisexual" could include male, female, or transgender bisexuals.…”
Section: Nbgi Reported Comments About Studymentioning
confidence: 99%
See 1 more Smart Citation